The Interactive Learning Model: A theory that assists the L2 learner in achieving self-awareness - Johnston, Christine A.; Klein, Gabriella B.; Johnston, Noah; Johnston, Joel (Glottodidactica, 2021)
This study uses the Interactive Learning Model theory to explore the nature of self-awareness within each of three L2 learners. Using the Learning Connections Inventory (LCI), a validated and reliable learning instrument, each participant identified their combination of learning patterns. The subjects then recalled specific L2 learning experiences, relating them in first person narratives. Next, each subject composed anecdotes and reflections based on their narratives. They also participated in one-on-one interviews in which they described their learning experiences during basic L2 learning activities: vocabulary, grammar, writing, conversation, and passive listening during movies, live theatre, spectator sports, and television. Our analysis of the LCI outcomes and selfreported learning experiences demonstrated that the self-awareness gained from understanding their combination of learning patterns and expanded by the self-reflection activities, increased the participants’ ability to articulate the nature of their self-awareness and to identify evidence of their growth in self-awareness during L2 learning.